Praktik Gharar Pada Hubungan Bisnis UMKM-Eksportir Furnitur di Jepara - Lidnillah, Achmad Hijri; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine the type of gharar practiced in cooperation between Small and medium industry exporters of furniture to the furniture in Jepara district.This study used a qualitative descriptive approach with a case study strategy.Determinating techniques for informants in this study using snowball sampling. Data collected through interviews with research subjects and direct observation of the research object. The analysis technique used is descriptive analysis by using the method of data analysis and describes the results of interviews and direct observation.The results of this study indicate that gharar is practiced in the cooperation between the Small and medium industry with the company exporting furniture is unclear at the end of the time limit on credit payments by companies exporting furniture to the Small and medium industry as suppliers of goods to the company.